Enhancing Commuter Accessibility in Tacloban’s University Belt, Philippines - Entatano, Hannah Marie; Lamayo, Chester Brian; Romero, Lorenzo Jr.; Montaño, Pamela; Pepe, Allen (Journal of Interdisciplinary Perspectives, 2025)
Public transportation is critical in supporting urban mobility, providing economic benefits, and reducing environmental impacts. However, Tacloban City, particularly its University Belt Area, faces significant transportation challenges, including traffic congestion, inadequate infrastructure, and accessibility disparities among transit stops. While many studies broadly explore urban transportation systems, this research distinguishes itself by addressing accessibility within a localized context, combining commuter perceptions with traditional metrics. By focusing on Tacloban City’s University Belt Area, this study fills a gap in understanding transit accessibility in densely populated, commuter-reliant urban areas. This research evaluates six transit stops—TS-1 (LNU), TS-2 (LNHS), TS-3 (EVSU), TS-4 (Card Bank), TS-5 (LBC), and TS-6 (LVD)—through data collection from 599 respondents and 10 days of traffic volume counts. Using Geographic Information System (GIS) heatmaps and statistical tools like Spearman's Correlation, ANOVA-Kruskal Wallis, and Dunn's Test, the study identifies patterns and variations in accessibility during peak and off-peak hours. Findings reveal that 83% of commuters experience waiting times of 10–20 minutes during peak hours at underperforming stops like TS-5, compared to 5–10 minutes at high-performing stops like TS-2 and TS-3. Additionally, 60% of TS-5 users report travel times exceeding 5 minutes, unlike other stops where travel times are predominantly within 0–5 minutes. Recommendations include increasing public transport availability, optimizing schedules, and enhancing pedestrian pathways and transit facilities. The findings provide actionable insights for policymakers to prioritize investments and design equitable urban transportation solutions, contributing to a more sustainable and accessible transportation system for Tacloban City and serving as a framework for addressing similar challenges in other urban areas.